Anticlusterin treatment of breast cancer cells increases the sensitivities of chemotherapy and tamoxifen and counteracts the inhibitory action of dexamethasone on chemotherapy-induced cytotoxicity - Redondo-Bautista, Maximino; Téllez-Santana, Teresa; Roldán Cardenete, María José; Serrano-Garballo, Alfonso; García Aranda, Marilina; Gleave, Martin E; Hortas Nieto, María Luisa; Morell Ocaña, Miguel (BMC Springer Nature, 2007)
Introduction: Overexpression of the apoptosis-related protein clusterin is associated with breast cancer development and tumor progression. We describe the use of clusterin-specific antisense oligonucleotides and antibodies to sensitize breast carcinoma cells to anticancer drugs routinely used in breast cancer therapy. Methods: MCF-7 and MDA-MB-231 cells were treated with the oligonucleotide or antibody, chemotherapeutic agents (doxorubicin or paclitaxel), tamoxifen, or with combinations of these. Results: Treatments that include antisense clusterin oligonucleotide or antibody to clusterin have been shown to reduce the number of viable cells more effectively than treatment with the drugs alone. We also demonstrate that dexamethasone pretreatment of breast cancer cell lines inhibits chemotherapy-induced cytotoxicity and is associated with the transcriptional induction of clusterin. However, anticlusterin treatment increases chemotherapy-induced cytotoxicity, even in the presence of glucocorticoids, suggesting a possible role for these proteins in glucocorticoid-mediated survival. Conclusion: These data suggest that combined treatment with antibodies to clusterin or antisense clusterin oligodeoxynucleotides and paclitaxel, doxorubicin, or tamoxifen could be a novel and attractive strategy to inhibit the progression of breast carcinoma by regulation of the clusterin function. Moreover, glucocorticoid activation in breast cancer cells regulates survival signaling by the direct transactivation of genes like clusterin which encode proteins that decrease susceptibility to apoptosis. Given the widespread clinical administration of dexamethasone before chemotherapy, understanding glucocorticoid-induced survival mechanisms is essential for achieving optimal therapeutic responses.
Keywords: Mamas - Cáncer; Clusterin; Breast Cancer; Treatment